The impact of the COVID-19 pandemic on the provision of speech therapy services in Bosnia and Herzegovina - Duranović, Mirela; Begić, Leila; Babic Gavrić, Branka; Lauc, Marijana (Specijalna edukacija i rehabilitacija, 2023)
Introduction. A newly discovered SARS-CoV-2 virus that causes an infectious disease called Coronavirus Disease 2019 (COVID-19) has spread around the world. Objectives. The study aims to explore the impact of the COVID-19 pandemic on speech-language pathologists (SLPs) clinical service delivery. Accordingly, this study aims to determine which modifications were used in the provision of speech-language pathology (SLP) services and which procedures were used by SLPs in their clinical practice in Bosnia and Herzegovina (B&H) during the third pandemic wave. The second aim of the study was to analyze how many SLPs from B&H used telepractice and what are the barriers to performing this type of work. Methods. The study included 107 SLPs, who voluntarily joined the survey, after sending the questionnaire directly to the e-mail or placing the questionnaire in online SLPs groups. The survey comprised questions to assess participants’ demographics, personal protective equipment, procedures, provision of telepractice, and barriers and limitations to telepractice implementation. Results. Results showed that 93.4% of SLPs reported they use measures to prevent and control the COVID-19 pandemic. Only 28% of SLPs used telepractice in their work, which is a very low rate. The majority of SLPs (59.2%) reported that they did not receive the appropriate education about using telepractice. Conclusion. The COVID-19 pandemic led to a change in service delivery by SLPs requiring them to modify their work or to provide services through telepractice.